Mullā Shamsā (d. 1654) on Atemporal Creation (ḥudūth dahrī) - El-Rouayheb, Khaled (Oriens, 2025)
The present article provides a new interpretation of the theory of ḥudūth dahrī associated with the Iranian philosopher Mīr Dāmād (d.1631) and his followers. Relying mainly on a treatise by Mīr Dāmād’s student Mullā Shamsā Gīlānī (d.1654), I emphasize the closeness of the theory to the view, advocated by Islamic theologians, that the world and time are not pre-eternal and came into existence ex nihilo. By contrast, I argue that the doctrine of "the primacy of essence" and Neoplatonic notions of "higher time" or "meta-time" are inessential to the theory.